2017
DOI: 10.1186/s12933-017-0566-y
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic retinopathy is associated with diastolic dysfunction in type 2 diabetic patients with non-ischemic dilated cardiomyopathy

Abstract: BackgroundTo investigate the association between diabetic retinopathy (DR) and myocardial dysfunction in patients with type 2 diabetes and dilated cardiomyopathy (dCMP).MethodsData were collected retrospectively from 89 patients with dCMP (46 with type 2 diabetes and 43 without diabetes) and no evidence of coronary artery disease. Echocardiographic parameters and laboratory data, including lipid profiles and fundus findings, were obtained from medical records. A left ventricular ejection fraction (LVEF) less t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 38 publications
0
7
1
Order By: Relevance
“…Echocardiographic studies have shown that T2D is associated with abnormalities of diastolic function independent of the presence of coronary artery disease . In addition, the presence of MiVD in patients with T2D also seems to be associated with the presence of diastolic dysfunction . It is possible that MiVD plays a role in the pathophysiology of incident HFpEF but, perhaps more importantly, that MiVD is a risk factor for development of HFpEF.…”
Section: Discussionmentioning
confidence: 99%
“…Echocardiographic studies have shown that T2D is associated with abnormalities of diastolic function independent of the presence of coronary artery disease . In addition, the presence of MiVD in patients with T2D also seems to be associated with the presence of diastolic dysfunction . It is possible that MiVD plays a role in the pathophysiology of incident HFpEF but, perhaps more importantly, that MiVD is a risk factor for development of HFpEF.…”
Section: Discussionmentioning
confidence: 99%
“…When prescribing a secondary oral hypoglycemic agent, its effects on vascular complications are an important consideration. We recently reported the association of DR with diastolic dysfunction in type 2 diabetic patients with cardiomyopathy [36], so efforts to prevent the progression of DR might also protect cardiac function. DPP4 inhibitors can protect against DR [16, 37], but their effect on DR remains controversial because they may aggravate vascular leakage [17].…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings quoted by Yoo Ri Chung et al, the E/A ratio, E or E/E′ratio, that represent diastolic dysfunction, were impaired in subjects with diabetic retinopathy compared to those without retinopathy. [17] Soichi Kurioka et al concluded that, almost all subjects had asymptomatic LVDD and that the severity of diabetic retinopathy was associated with LVDD in subjects with T2DM. [18] In the present study, diabetic subjects with microalbuminuria had significant lower values of E/A ratio, e', E'sr and high values of A, E/e', E/E'sr and peak TR jet velocity, compared to those without microalbuminuria.…”
Section: Resultsmentioning
confidence: 99%